1987
DOI: 10.1016/0014-5793(87)80380-0
|View full text |Cite
|
Sign up to set email alerts
|

[4,4′‐(Z)‐Dehydrophenylalanine]gramicidin S with stabilized bioactive conformation and strong antimicrobial activity

Abstract: Dehydrophenylalanine (ΔPhe) was incorporated into an antibiotic peptide gramicidin S (GS) in place of D‐Phe4,4′ to prepare an unsaturated analog. Conformational analysis with 1H‐NMR indicated that the unsaturated analog has much the same backbone conformation as that of natural gramicidin S as shown by NOE experiments. Studies on temperature dependences and on the chemical shift differences showed that the hydrogen bonds between Val‐NH and Leu‐CO in the unsaturated analog are strengthened by the incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…In order to explain the CD data, authors conclude that the helix contains a nonintegral number of residues per turn. CD studies on A'Phe-containing analogues of gramicidin (GS) 17,75 have also been reported. These results along with nmr data suggest that the A' Phe4,4' residues in [Az Phe4,4'] GS reinforce the GS-like 0-sheet conformation, allowing the retention of the strong antimicrobial activity for this analogue.…”
Section: Studiesmentioning
confidence: 96%
“…In order to explain the CD data, authors conclude that the helix contains a nonintegral number of residues per turn. CD studies on A'Phe-containing analogues of gramicidin (GS) 17,75 have also been reported. These results along with nmr data suggest that the A' Phe4,4' residues in [Az Phe4,4'] GS reinforce the GS-like 0-sheet conformation, allowing the retention of the strong antimicrobial activity for this analogue.…”
Section: Studiesmentioning
confidence: 96%
“…The presence of α,β‐dehydro residues in peptides confers altered bioactivity as well as increased resistance to enzymatic degradation 12. Dehydroresidues have been introduced in several bioactive sequences in order to obtain highly active agonist and antagonist analogs, and this modification has become one of the most promising methods to study structure‐function relationships in biologically active peptides 13–22. α,β‐Dehydroamino acid analogs of some peptide hormones like dehydroangiotensin,23 dehydrobradkynin,24 dehydrodermorphin,19, 20 dehydrosomatostatin,25 dehydrosubstance P fragments,22 dehydroenkephalin,21 and dehydrogramicidin S have been synthesized and their biological activity reported 26…”
Section: Introductionmentioning
confidence: 99%
“…Those unsaturated amino acids are also applicable for modification of the bioactive compounds, in order to obtain more active and less toxic analogous [37][38][39]. D-amino acids are also used to design new class of inhibitors of several types of enzyme [19,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%